The Correctional Programming For Inmate On Pre- And Post Release - Poonyasawat, Jiravoot (Huachiew Chalermprakiet Law Journal, 2022)
Abstract Correctional Department is the last agency of the criminal justice system which plays vital roles in protecting society from the dangerous people. Specifically, the correctional department is responsible for custody of prisoners in accordance with court judgments directly. These people are a prisoner, a convicted prisoner, a detained person, an entrusted person prisoner. Moreover, the correctional department has the duty to provide and develop the quality of life for prisoners. The correctional department provides the social welfares in various aspects. This is to help prisoners improve their behaviors and is able to return to society without recidivism. The procedure of prisoner rehabilitation in Thai correctional system begins with the prisoner classification process by the prisoner assessment. The prisoner assessment results are used for setting the sentence plan for individuals. This is to rehabilitate prisoners to be able to adjust their behaviors and return to society. This focuses on since the admission stage until the pre- release and post release stage. Prisoners will be improved their behaviors and supported in various aspects properly. Particularly, if the management of prisoner pre-release and post-release is effective, this will enhance the quality of life for prisoners. This will return the decent citizen to drive the social mechanism. It also reduces the recidivism rate in the future. Additionally, this guideline reduces the cost of managing inmates which has a positive effect on the inmates themselves and to society. Therefore, this study has studied the correctional management in the preparation of pre-release and post-release prisoner in abroad which consists of Canada, Japan and Singapore. These countries are an effective management model for the preparation of prisoners before getting release and after release. From the study, it was found that the three countries had effective guidelines for the preparation of pre-release and post-release prisoners. This resulted from law enforcement and effective management of the preparation of prisoners before release and after release. These guidelines are advantages to improve the Thai laws for prisoner pre - release and post release procedures. The researcher has suggested as follows: Law revisions are essential to effectively drive the pre-release and post-release process of prisoners. Therefore, there should improve the law to be appropriate. Specifically, improving the law to be consistent with the pre-release and post release procedure, including law of non-custodial measurements, law of helping prisoners, legal restrictions on occupation, law for the provision of rights and welfare assistance to inmates and ex-prisoners. This also includes that there is a specific law on pre-release and post-release procedures and defines the roles and duties of working. Management of pre - release and pose release procedure should be set with a variety of formats. This includes there should have the specific staff in conducting the pre - release and post - release procedure